The Effect of Implementing Hybrid Work on Work-Life Balance, Job Satisfaction, and Employee Wellbeing - Nugroho, Arieko Widyastomo; Desiana, Putri Mega (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This study aims to analyze the effect of implementing a Hybrid Working Arrangement policy on work-life balance, employee satisfaction, and employee well-being at PT ABC. The methodology used is a quantitative approach, with data collection through a survey distributed to 255 employees of PT ABC. Data analysis was carried out using the Structural Equation Modeling (SEM) method. The results of this study indicate that hybrid working arrangements do not have a significant direct effect on employee well-being. This study also found that there is a direct effect of hybrid working arrangements on well-being through increasing work-life balance and employee satisfaction. These findings provide important insights for the management of PT ABC and other companies in implementing hybrid working policies to improve employee wellbeing.